Determinants of Sugar-Sweetened Beverage Consumption Among the Saudi Adults: Findings From a Nationally Representative Survey - Al-Hanawi, Mohammed Khaled; Ahmed, Moin Uddin; Alshareef, Noor; Qattan, Ameerah Mohammad Nour; Pulok, Mohammad Habibullah (Frontiers in Nutrition, 2022)
Background: Saudi Arabia is the fifth largest consumer of calories from sugar-sweetened beverages (SSB) in the world. However, there is a knowledge gap to understand factors that could potentially impact SSB consumption in Saudi Arabia. This study aims to examine the determinants of SSB in Saudi Arabia. Methods: The participants of this study were from the Saudi Health Interview Survey of 2013, recruited from all regions of Saudi Arabia. A total of 10,118 survey respondents’ data were utilized in this study who were aged 15 years and older. Our study used two binary outcome variables: weekly SSB consumption (none vs any amount) and daily SSB consumption (non-daily vs. daily). After adjusting for survey weights, multivariate logistic regression models were applied to assess the association of SSB consumption and study variables. Results: About 71% of the respondents consumed SSB at least once weekly. The higher likelihood of SSB consumption was reported among males, young age group (25-34 years), people with lower income (< 3000 SR), current smokers, frequent fast food consumers, and individuals watching television for longer hours (≥ 4 hours). Daily vegetables intake reduced the likelihood of SSB consumption by more than one-third. Conclusions: Three out of four individuals aged 15 years and over in Saudi Arabia consumes SSB at least once weekly. A better understanding of the relationship between SSB consumption and demographic, socioeconomic, and behavioral factors is necessary for the reduction of SSB consumption. The findings of this study have established essential population-based evidence to inform public health efforts to adopt effective strategies to reduce the consumption of SSB in Saudi Arabia. Interventions directed towards education on the adverse health effect associated with SSB intake are needed.